The Lala kalimba: the correlation between instrument and style. - Van Dijk, Marcel (International Library of African Music, 2010)
Once I got the opportunity to go to Zambia to conduct field research and stay with the Lala people for several months, I discovered much to my delight that the kalimba - the lamellophone found there - took an important place in the musical culture of the Lala. THe richness and variety of the music and the open-heartedness of the musicians turned out to be a revelation to me. Moreover, it became clear that through the kalimba other aspects of the Lala society could be exposed.
Keywords: African Music